Keterlibatan Pemerintah Kota Tanjungpinang dalam Upaya Penanggulangan Kemiskinan - Afriyadi Afriyadi; Masayu Vrisaliani; Natasya Saffa Adesti; Raja Fitriana; Suci Alya; Ahwe Eliza Nanda (Kajian Ekonomi dan Akuntansi Terapan, 2024)
Poverty is a common problem that continues to be faced by every region in the world, especially in remote areas, which causes an increase in poverty rates. To overcome the impact of the COVID-19 pandemic, serious efforts are needed to stop its spread, which must be supported by all levels of society by complying with government regulations. Because poverty reflects the inability to meet needs, poverty data is an important indicator in social analysis, especially for policy makers. This research aims to describe and analyze the role and policies that have been implemented by the Tanjungpinang City Government in efforts to reduce poverty. This research uses qualitative methods with literature study as a data collection technique. The conclusion that can be obtained from this research is that a comprehensive evaluation of these programs shows a reduction in the number of poor people and an increase in welfare as a result of the various initiatives implemented. Integrated health, education, skills training and social assistance programs have also helped in providing holistic solutions in overcoming the problem of poverty.